The uses and users of design process models in organizations - Costa, Daniel Guzzo da (2016)
The use of design process models is of great importance for developing better products. Indeed, it is one of the factors that may differentiate the best companies from the rest. However, their adoption in companies is declining. Usefulness and usability issues may be responsible for process models not to meet the needs of its users. The goal of this research is to provide deeper understanding of the users needs of design process models. Three main perspectives are provided: (1) why organizations use process models, (2) who are the users of process models, and (3) how the context of use of process models is. The research methodology adopted was the Design Research Methodology (DRM). Three stages were performed: (i) Research Clarification, (ii) Descriptive Study I, and (iii) Prescriptive Study. In the first stage, an initial literature review was carried out to collect evidences of why researching process models and their users needs is relevant for the design theory. During the second stage (Descriptive Study I), literature was reviewed to identify the purposes of use of design process models and its potential users; a focusgroup section with 24 subject matter experts was carried out to evaluate these purposes and identify process model users; and, lastly, a case study was perfomed to investigate the context of use of design process models in one organization and to portray the profile of the core users. Finally, the third stage (Prescriptive Study) aimed to uncover directions for organizations develop user-centered design process models. Four main results were achieved through this research. The first result is a deep understanding of three types of application of the design process models: (a) develop the design activity, (b) manage the design project, and (c) improve the design process. The purposes for these aplications were investigated and their level of importance were revealed. In addition, it was mapped the core users of process models for the three applications. The second result is the definition of the context of use of the models.Three dimensions of the context were depicted: the product, the design process, and the organizational structure. The third result is the set of users profiles. Empathy Maps were elaborated to represent the profiles of product engineers, project managers, and technical leaders. The last result consists in recommendations regarding the content provided to users and the process models system design. Finally, industrial practitioners will benefit from this research once it was provided evidences that the activity development application type is not properly considered in organization and that important users needs are not getting proper attention in the current models. Therefore, they will be able to make use of the recommendations outlined here.